Design Of Web-Based E-Report Information System For Paud At-Taqwa Using Laravel Framework - Ahmad Altaf Hali; Umar Mansyuri; Rahadian Arief (Brilliance: Research of Artificial Intelligence, 2025)
Manual student report card management at PAUD At-Taqwa poses critical challenges, including significant time inefficiency in daily assessments, the high risk of physical data loss, and limited parental access to timely child development information. This research aims to design and build a web-based e-report card information system to resolve these issues by integrating the entire assessment workflow into a single, centralized digital platform. The system was developed using the waterfall model, which includes the stages of requirements analysis, system design using Unified Modeling Language (UML), implementation, and functional testing. Built with the Laravel Framework (MVC) and a MySQL database, the system's functionality was validated through black box testing. The research resulted in a functional e-report card system with three distinct, permission-based access roles: Administrator, Teacher, and Parent. The Administrator manages all master data, including user accounts and class assignments. The Teacher role is equipped with tools for the digital recording of daily student progress. A key innovation is an AI-assisted feature, powered by the Gemini API, that automatically generates draft narrative reports based on collected daily notes, significantly reducing the teacher's workload. The Parent role provides a secure portal for real-time monitoring of their child's activities and for viewing digital report cards. It is concluded that the system successfully transforms the reporting process into an efficient digital workflow, effectively improving teacher efficiency, enhancing information transparency for parents and institution.